Analisis Instrumen Tes Kemampuan Berpikir Kritis Berbantuan Game Physics Quiz Adventure pada Materi Energi dan Sumber Energi Terbarukan - Paresti, Ananda Nurma; Sunarti, Titin (Universitas Negeri Surabaya, 2024)
In order to achieve success in the 21st century, students need to equip themselves with four essential learning competencies: think critically, have a good understanding, be able to collaborate and communicate well, and develop their creativity. Students who think critically are able to draw conclusions, interpret information, analyze, evaluate, explain and control their own thinking processes. This research aims to analyze theoretical validity by experts consisting of the content, construct and language domains as well as reliability and analyze empirical tests on the validity, reliability, level of difficulty and differentiability of each critical thinking ability test instrument. Limited trials were carried out in this research from class X students at SMA Khadijah Surabaya involving 91 students. Critical thinking test instrument with 6 questions in multiple choice form. According to the research results, the theoretical validity in the language domain was 4.33; the construct domain is 4 and the content domain is 4.33 with a very valid category. Then for theoretical reliability using the percentage of agreement calculation, the results were 87%, which is in the very high category. Then, a limited trial was carried out and obtained empirical validity of the question items of 0.397 to 0.528 with the six question items declared valid. Then, the instrument reliability obtained was r11 of 0.250 and was declared reliable. Then, the level of difficulty for the six question items ranges from 0.49 to 0.55 in the medium category. Then, the differential power of the six question items ranges from 0.44 to 0.68 in the good category. Thus, by analyzing the criteria for the questions consisting of validity, reliability, level of difficulty and differentiation, it was found that the six question items met the requirements and could be used. Keywords: Validity, level of difficulty, critical thinking, reliability, energy and renewable energy sources and different power